Analysis of Measures to Control Grain Moisture and Reduce Energy Consumption in Grain Processing - Docent:Safarov Askhar Asadullayevich; Docent:Mukhimov Ziyoviddin Ma’murovich; Jurayev Fayzulla Ashurovich (Genius Journals, 2023)
This article discusses one of the main quality indicators of grain, grain moisture and grain moisture control, grain moisture measurement methods, the role and importance of grain moisture in processing, and analysis of measures to reduce electricity consumption.
Keywords: grain moisture; the process of moistening and moistening of grain; the relationship of grain with water during the period of moisture transfer to grain